PENGEMBANGAN LKS FISIKA TERINTEGRASI KARAKTER BERBASIS KONTEKSTUAL UNTUK SMP/MTs - Zanah, Miftakhul; Partono, Partono; Alarifin, Dedy Hidayatullah (Universitas Muhammadiyah Metro, 2021)
Abstract: The purpose of this researcher is to determine the feasibility level of developing contextual-based integrated character worksheets on the subject matter of IPA and its observations for students of class VII SMP / MTs in padangratu. This research is included in the type of Research and Development (R&D) development research. The method used is ADDIE which stands for analysis, design, development, implementation, and evaluation. The level of feasibility of this development product seen from the results of the validation showed very reasonable criteria, the results of the feasibility percentage of material experts were 86.67%, percentage of language experts 88.33%, percentage of design experts 87.49%, and percentage of student responses 74.21%. Based on the results of the summary data recapitulation that has been done shows the feasibility of contextual-based worksheets with maternal object material and its observations, on material experts amounted to 86.67%, percentage of language experts 88.33%, percentage of design experts 87.49%, and percentage student response 74.21%. From the results of expert validation and student response shows the percentage> 60 so that the student activity sheet (LKS) Physics is declared very feasible to be used in learning.Keywords: characters, contextual, development of student activity sheets (LKS).